PROFESSIONAL-ORIENTATION WORK IN LESSONS TECHNOLOGIES IN A SECONDARY SCHOOL WITH A 12-YEAR-OLD TERM (Pedagogy of Higher and Secondary Education, 2008)
In the article the basic aspects of professionally-orientation work are examined on the lessons of labour studies in modern terms. The role of teacher is shown in forming of professional self-determination of students at the study of discipline the «Labour studies» insecondary comprehensive schools.